Cellular neural network training by ant colony optimization algorithm [Karinca kolonisi optimizasyon algoritmasi ile hücresel yapay sinir aǧi eǧitimi] - (:unkn) unknown (My University, 2010)
Cellular Neural Networks (CNN) having parallel processing capabilities presenst important advantages in image processing applications. The coefficients of the template matrices and the threshold values of CNN should be optimized to obtain the desired output image. The learning algorithms designed for classical feed forward neural networks are not suitable for CNN due to its dynamic architecture. Researchers are still working on development of generalized learning algorithms for CNN. In this study, the CNN training is realized by ant colony optimization (ACO) technique. The results obtained by trained CNN show that ant colony based learning algorithm is very successful for image feature extraction problems such as edge, corner, vertical and horizontal edge detections. ©2010 IEEE.